Komunikasi Kelompok Komunitas Film Fakultas Ilmu Komunikasi (Koffi) Universitas Bhayangkara Jakarta Raya dalam Mengatasi Konflik - Syafrina, Annisa Eka (Sekolah Tinggi Ilmu Komunikasi Inter Studi, 2023)
Abstract. Groups are an important part of our daily life. However, groups cannot avoid conflict. Therefore, in supporting the success of the group, communication is needed. However, in the process of communication that occurs in groups, it is not uncommon for conflicts to arise. Conflict is something that cannot be avoided in group life. This study aims to find out how the communication of the Film Community Group of the Faculty of Communication Studies (Koffi) Bhayangkara University Jakarta Raya in overcoming conflict. By using a qualitative research method with a descriptive type that describes the current state of the research object, based on the facts that appear. Researchers conducted interviews with informants related to research. The results of the study show that Koffi's group communication uses a morphogenic system, namely the group is open to change, accepts new ideas and ways of interacting, and members are willing to check their assumptions and perspectives. The group system of interaction and emotional intelligence in this group shows that behavior also influences the success of the group. In addition, the groupthink and knowledge management of this group is quite good because each member of the main group has been assigned their respective duties and responsibilities. and deepen the scope of research so that the data obtained is better. In addition, it is recommended to take a different approach, for example using a quantitative approach so that the research results are more accurate.